RETRACTED: The F Word among Children - Puji Rahayu; Slamet Setiawan (Pioneer: Journal of Language and Literature, 2021)
RETRACTED Following a rigorous, carefully concerns and considered review of the article published in PIONEER: Journal of Language and Literature to article entitled “The F Word among Children: Case of Javanese Children” Vol 13, No 2, pp. 148-161, December 2021, DOI: https://doi.org/10.36841/pioneer.v13i2.983. This paper has been found to be in violation of the PIONEER: Journal of Language and Literature Publication ethics and has been retracted. The article contained redundant material, the editor investigated and found that the paper published in Language Circle: Journal of Language and Literature, Vol. 16, No. 1 (2021), pp. 110-117, URL: https://journal.unnes.ac.id/nju/index.php/LC/article/view/29690, entitled "The ‘F Word’ Among Bilingual Children in Their First Language". The document and its content has been removed from PIONEER: Journal of Language and Literature, and reasonable effort should be made to remove all references to this article.